2008
DOI: 10.1007/s10654-007-9216-0
|View full text |Cite
|
Sign up to set email alerts
|

Prior health care utilization as a potential determinant of enrollment in a 21-year prospective study, the Millennium Cohort Study

Abstract: Results obtained from self-reported health data may be biased if those being surveyed respond differently based on health status. This study was conducted to investigate if health, as measured by health care use preceding invitation, influenced response to invitation to a 21-year prospective study, the Millennium Cohort Study. Inpatient and outpatient diagnoses were identified among more than 68,000 people during a one-year period prior to invitation to enroll. Multivariable logistic regression defined how dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…Previous studies have shown these cohort data to be reliable and survey response to be uninfluenced by poor health status. 15,17,[37][38][39][40][41][42][43] We believe that these results are generalizable to the entire US military because of the large sample size and population-based random sampling methods used. To some extent, results may also be generalizable to any population of healthy young adults.…”
Section: Limitations and Strengthsmentioning
confidence: 77%
“…Previous studies have shown these cohort data to be reliable and survey response to be uninfluenced by poor health status. 15,17,[37][38][39][40][41][42][43] We believe that these results are generalizable to the entire US military because of the large sample size and population-based random sampling methods used. To some extent, results may also be generalizable to any population of healthy young adults.…”
Section: Limitations and Strengthsmentioning
confidence: 77%
“…The population-based design allowed for assessment among all service branches and components (active duty, Reserve, and National Guard), including those no longer serving in the military. Although limitations exist with self-reported data, previous analyses have shown that Millennium Cohort participants self-report data reliably, well represent the U.S. military, and were not influenced to participate on the basis of previous health (53)(54)(55)(56)(57)(58)(59)(60). Additional strengths of the study include the large sample size that provided statistical power and the ability to control for multiple confounders.…”
Section: Discussionmentioning
confidence: 98%
“…However, multiple investigations of possible reporting and selection biases in baseline Millennium Cohort data suggest reliable reporting, minimal response bias, and a representative sample of military personnel, including deployers. 14,15,[30][31][32][33][34][35]37,73,81 Use of the PHQ along with the DSM-IV criteria has shown to correlate well with a physician's assessment of depression symptoms, 32 and the PHQ is internally valid in Millennium Cohort members. 32 However, the use of a standardized instrument for self-reported data as a surrogate for depression diagnosis is imperfect.…”
Section: Discussionmentioning
confidence: 99%